A Comparison of Parent, Teacher, and Youth Ratings on the Inventory of Callous–Unemotional Traits. (January 2023) - Matlasz, Tatiana M.; Frick, Paul J.; Clark, Julia E.
The current study compared the validity of self-, parent-, and teacher-report versions of the Inventory of Callous–Unemotional Traits (ICU), a widely used measure of callous–unemotional (CU) traits, at several different ages. Participants ( N = 236, 60.6% girls) were children in Grades 3, 6, and 8 ( M age = 11.55, SD = 2.23) from a public school system in the southern United States. We tested the association of all three ICU versions with several validators: parent- and teacher-reported conduct problems, peer nominations of characteristics associated with CU traits, and sociometric peer nominations of social preference. Results revealed an interaction between the ICU version and grade in the overall level of CU traits reported, with teacher-report leading to the highest ratings in sixth grade and being higher than parent-report in third grade. Furthermore, the validity of the different versions of the ICU varied somewhat across grades. Specifically, findings support the validity of both teacher- and self-report in third grade, but self-report was the only version to show strong validity in the eighth grade.